2020
DOI: 10.1186/s43045-020-00028-x
|View full text |Cite
|
Sign up to set email alerts
|

Burnout syndrome among psychiatrists in Egyptian mental health hospital

Abstract: Background Burnout is a special type of work-related stress—a state of physical or emotional exhaustion that also involves a sense of reduced accomplishment and loss of personal identity (Lancet 388:2272-2281, 2016). Burnout is a syndrome of state of emotional exhaustion, depersonalization, and feelings of low personal accomplishment (Maslach C and Jackson S, Maslach burnout inventory manual, 1986). Burnout syndrome leads to severe problems. It may cause psychoso… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(6 citation statements)
references
References 51 publications
0
4
0
2
Order By: Relevance
“…Intensive care unit (ICU) physicians and were extremely high among Egyptian Psychiatrists. [17][18][19] Burnout in medicine is gaining much attention with a number of studies showing physicians are at increasing risk of burnout symptoms.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Intensive care unit (ICU) physicians and were extremely high among Egyptian Psychiatrists. [17][18][19] Burnout in medicine is gaining much attention with a number of studies showing physicians are at increasing risk of burnout symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Another study found residents to have a high (81%) rate of emotional burnout (EE) as well as high rates (64%) of depersonalization (DP). Emotional exhaustion (EE) rates of burnout were 50% among physicians in Aswan (a southern Egyptian city) and were as high as 68.2% among Egyptian Intensive care unit (ICU) physicians and were extremely high among Egyptian Psychiatrists 17‐19 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Define-se burnout como algo que parou de funcionar por exaustão de energia no trabalhador em decorrência da resposta a estressores crônicos da prática do trabalho; descrevendo-se por sinais de exaustão emocional, despersonalização e baixa realização no trabalho (Porciuncula, et al, 2020;Dubale, et al, 2019;Abu Zied, et al, 2020).…”
Section: Introductionunclassified
“…Evidencia-se a ocorrência de burnout em trabalhadores de diversas áreas; mas principalmente nas profissões com atividades próximas aos clientes; como professores, bancários e trabalhadores da saúde e enfermagem, entre outros (Porciuncula, et al, 2020;Abu Zied, et al,2020;Dorneles, Dalmolin, Andolhe, Magnago & Lunardi, 2020).…”
Section: Introductionunclassified